A novel gypsum-based slurry composite rock wool clean board core material and preparation method thereof
By using gypsum-based slurry and modified glass fibers in the clean board core material, the existing clean board core material is solved, the problems of pollution and aging in the production process are improved, the product strength and fire resistance are achieved, and an efficient and environmentally friendly production process is achieved.
Patent Information
- Application Number
- CN202410901750.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-07-05
AI Technical Summary
During the production process, VOCS emissions pollute the environment, pose aging risk, combustion grades are not up to Class A, overall strength is low, easy to deform, and it is difficult to produce large-size boards, and it is difficult to build on-site splicing.
The gypsum-based slurry is directly poured on the A-level insulation material, and the integrated synthesis is automated. Instead of the traditional glue coating and paste method, modified glass fiber is added to the gypsum-based slurry and embedded into the alkali-resistant glass fiber mesh.
The strength, fire resistance, thermal insulation and corrosion resistance of the clean board core material are improved, and the production efficiency is improved, solving the problems of pollution, aging and insufficient strength in traditional technologies.
Smart Images

Figure BDA0004930660620000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a novel gypsum-based slurry composite rock wool clean board core material and a preparation method thereof. Background Art
[0002] Clean board (also known as purification board) is a composite board made of galvanized and color-coated materials as panel materials. Clean board has many advantages, good fire resistance, heat preservation and sound insulation, good compression resistance, flat surface, good rigidity, dustproof and antibacterial effects, and environmentally friendly and non-toxic. Therefore, clean board is often used in purification engineering fields with strict environmental requirements, such as electronics, electrical appliances, medicine, food, scientific research and other industries.
[0003] At present, the common core materials of clean boards are glass magnesium board + rock wool products, gypsum board + rock wool products, magnesium oxysulfide materials, etc. Among them, glass magnesium board and gypsum board are non-combustible materials, and need to be bonded to both sides of the rock wool board with organic glue. During the production process, VOCS emissions pollute the environment, there is an aging risk in the later stage, and it does not reach Class A non-combustible materials; magnesium oxysulfide core material is two pieces of magnesium oxysulfide boards with single-sided grooves bonded together with glue, and its combustion level does not reach Class A. In addition, the current clean boards have low overall strength, easy deformation, and cannot produce large-size boards, and on-site splicing construction is difficult.
[0004] Therefore, it is necessary to provide a new type of gypsum-based slurry composite rock wool clean board core material and a preparation method thereof. Summary of the invention
[0005] In view of the problems of the prior art, the purpose of the present invention is to provide a new type of gypsum-based slurry composite rock wool clean board core material and a preparation method thereof. The product is prepared by directly pouring the gypsum-based slurry on the A-class thermal insulation material, and automatically synthesizing it in one piece, which replaces the traditional clean board core material method of gluing and pasting the board on both sides of the thermal insulation material, thereby improving production efficiency. The obtained clean board core material has high strength, is not easy to deform, has strong fireproof effect, and is excellent in thermal insulation and corrosion resistance.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A gypsum-based slurry composite rock wool clean board core material comprises: a rock wool core board, and upper and lower panels formed by pouring gypsum-based slurry on both sides of the rock wool core board and embedding alkali-resistant glass fiber mesh; wherein,
[0008] The gypsum-based slurry contains modified glass fiber; the modified glass fiber is prepared by using glass fiber as raw material and sequentially modified by a double-bond silane coupling agent and 4-phenyl-3-butenoic acid.
[0009] In some specific embodiments, the mass ratio of the gypsum-based slurry to the glass fiber mesh in the upper and lower panels is 100:(1-1.5); preferably, the mass ratio of the gypsum-based slurry to the glass fiber mesh in the upper and lower panels is 100:(1-1.3).
[0010] In some specific embodiments, the thickness ratio of the upper and lower panels to the rock wool core board is 1:(3-8); preferably, the total thickness ratio of the upper and lower panels to the thickness of the rock wool core board is 1:(3-6).
[0011] In some specific embodiments, the mass per unit area of the alkali-resistant glass fiber mesh is ≥130 g / m 2 Preferably, the mass per unit area of the alkali-resistant glass fiber mesh is 130 to 160 g / m 2 .
[0012] In some specific embodiments, the rock wool core board is formed by staggered laying of rock wool strips; the rock wool strips are commercially available products or homemade in the laboratory; the preparation steps of the homemade rock wool strips in the laboratory are as follows:
[0013] The basalt is melted at high temperature and prepared into cotton-like fibers with a diameter of 4 to 7 μm by high-speed centrifugation. Phenolic resin is added to the cotton-like fibers as a binder, and the amount of phenolic resin is 8 to 10% of the mass of the cotton-like fibers. Then, rock wool strips are obtained by pendulum, pleating and drying.
[0014] In some specific embodiments, the double bond-containing coupling agent is selected from at least one of vinyltrimethoxysilane, vinyltriisopropoxysilane, and vinyltriethoxysilane.
[0015] In some specific embodiments, the mass ratio of the double bond-containing coupling agent to the glass fiber is (7-12):100, and the preferred mass ratio is (8.5-10):100.
[0016] In some specific embodiments, the mass ratio of 4-phenyl-3-butenoic acid to glass fiber is (2-5):100, and preferably the mass ratio is (3-3.5):100.
[0017] Furthermore, the modified glass fiber is prepared by the following method:
[0018] (1) dissolving a double bond-containing coupling agent in 8 to 10 times by weight of anhydrous ethanol to obtain a coupling agent solution;
[0019] (2) adding the coupling agent solution to the glass fiber to react, and taking out and drying after the reaction is completed to obtain the coupling agent modified glass fiber;
[0020] (3) Add 4-phenyl-3-butenoic acid into water, add a coupling agent to modify the glass fiber, and an initiator to react. After the reaction is completed, take out and dry to obtain the modified glass fiber.
[0021] Preferably, in the step (2) of preparing the modified glass fiber, the reaction time is 2 to 4 hours.
[0022] Preferably, in the preparation step (3) of the modified glass fiber, the initiator is selected from a peroxide initiator or an azo initiator, and the amount of the initiator used is 0.01 to 0.05% of the amount of glass fiber used; more preferably, it is at least one of diisopropylbenzene peroxide, dibenzoyl peroxide, and azobisisobutyronitrile.
[0023] Preferably, in the step (3) of preparing the modified glass fiber, the reaction time is 2 to 4 hours.
[0024] In some specific embodiments, the gypsum-based slurry further comprises gypsum, starch ether, rubber powder, additives and auxiliary agents.
[0025] Furthermore, the gypsum is selected from at least one of phosphogypsum powder, desulfurized gypsum powder and natural gypsum; preferably, the gypsum is a combination of α-semihydrated desulfurized gypsum powder and phosphogypsum powder in the desulfurized gypsum powder; the mass ratio of the α-semihydrated desulfurized gypsum powder to the phosphogypsum powder is 1:(0.2-0.35); more preferably, the gypsum is selected from a combination of α-semihydrated desulfurized gypsum powder and phosphogypsum powder in a mass ratio of 1:(0.27-0.3).
[0026] Furthermore, the starch ether is at least one of hydroxyalkyl starch ether, carboxymethyl starch ether and cationic starch ether; the molecular weight of the starch ether is 50,000 to 200,000; and the degree of substitution of the starch ether is 0.3 to 2.0.
[0027] Furthermore, the starch ether is selected from a composition of hydroxyalkyl starch ether and cationic starch ether in a mass ratio of 10:(1.5-4); wherein,
[0028] The hydroxyalkyl starch ether is preferably hydroxyethyl starch ether or hydroxypropyl starch ether; the degree of substitution of the hydroxyalkyl starch ether is 0.7 to 1.2, and the molecular weight is 100,000 to 200,000;
[0029] The cationic starch ether is preferably prepared by etherifying corn starch using 3-chloro-2-hydroxypropyltrimethylammonium chloride as an etherifying agent; the degree of substitution of the cationic starch ether is 0.3-0.6 and the molecular weight is 50,000-100,000.
[0030] Furthermore, the auxiliary agent is selected from a water reducing agent and / or a retarder.
[0031] Preferably, the water reducer is selected from at least one of naphthalene water reducer, aliphatic water reducer, amino water reducer and polycarboxylic acid water reducer; the retarder is selected from at least one of citric acid, sodium citrate, tartaric acid, potassium tartrate, acrylic acid and sodium acrylate.
[0032] Furthermore, the gypsum-based slurry comprises the following raw materials in proportion by weight: 900-980 parts of gypsum, 0.3-0.8 parts of starch ether, 1-4 parts of rubber powder, 2-4 parts of water reducer, 2-4 parts of retarder, 1-5 parts of glass fiber, and 400-600 parts of water.
[0033] Preferably, the gypsum-based slurry comprises the following raw materials in proportion by weight: 950-960 parts of gypsum, 0.45-0.6 parts of starch ether, 2-3 parts of rubber powder, 3-3.5 parts of water reducer, 3-3.5 parts of retarder, 2.5-3.5 parts of glass fiber, and 500-560 parts of water.
[0034] On the other hand, the method for preparing the above-mentioned gypsum-based slurry composite rock wool clean board core material comprises the following steps:
[0035] (1) mixing the components in the gypsum-based slurry to obtain a dry powder mixture, and then adding water to mix to obtain a gypsum-based slurry;
[0036] (2) Laying the first layer of glass fiber mesh and pouring gypsum slurry to form the upper panel;
[0037] (3) placing rock wool strips on the upper panel surface to form a rock wool core panel;
[0038] (4) Laying a second layer of glass fiber mesh, pouring gypsum slurry on the surface of the rock wool core board to form a lower panel, and drying it to obtain the gypsum-based slurry composite rock wool clean board core material.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1. The clean board core material of the present invention is composed of a rock wool core material and a gypsum-based slurry poured on both sides of the rock wool core material and embedded in a glass fiber mesh, which is automatically synthesized in one piece, thereby solving the problem of using manual or equipment glue coating and compounding methods for traditional clean board core materials, and improving production efficiency.
[0041] 2. The rock wool core board of the clean board core material of the present invention is formed by staggered placement of rock wool strips. The staggered interlocking is beneficial to the stability of the thermal insulation material, and even if it is cut, it will be firmly and tightly interlocked.
[0042] 3. The clean board core material of the present invention has high strength, strong fireproof effect, thermal insulation and excellent corrosion resistance through the cooperation of individual components.
[0043] 4. The modified glass fiber is added to the gypsum-based slurry of the present invention to overcome the problem that ordinary glass fiber cannot be evenly dispersed in the gypsum-based slurry, resulting in uneven strength of the upper and lower panels, thereby causing problems such as board cracking and board breaking. The compatibility of the glass fiber modified in two steps with gypsum is improved, and the dispersibility in the gypsum-based slurry is improved, which improves the mutual bonding force of the components in the gypsum-based slurry and the strength of the upper and lower panels, thereby improving the strength of the clean board core material, acid and alkali corrosion resistance and fire resistance; the glass fiber modified with 4-phenyl-3-butenoic acid also helps to improve the thermal insulation performance of the clean board.
[0044] 5. The present invention selects desulfurized gypsum and phosphogypsum as the main materials of the gypsum-based slurry, which helps to further improve the strength, acid and alkali corrosion resistance and thermal insulation performance of the clean board.
[0045] 6. Adding starch ether to the gypsum-based slurry of the present invention can improve the construction performance of the gypsum-based mortar. Selecting a specific starch ether can help to increase the strength of the clean board and improve the thermal insulation performance. DETAILED DESCRIPTION
[0046] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0047] The cationic starch ether of the present invention is prepared by using the existing technology, and its preparation method is not particularly limited. Any method that can achieve the degree of substitution of the obtained cationic starch ether within the required range can be adopted. In the following specific embodiment, the cationic starch ether is prepared by the following method: 100g corn starch is added to a mixed solution of 200g water and isopropanol (mixing mass ratio is 5:95), 10g sodium hydroxide is added to buffer, and stirred for 60min; then heated to 70°C, 2g hydrogen peroxide (50%) is added to the solution and stirred for 6h; 1g sodium hydroxide is added, and a certain amount of 3-chloro-2-hydroxypropyltrimethylammonium chloride is added according to the required degree of substitution, and the reaction is continued to stir for 2h. After the reaction is completed, acetic acid is added for neutralization; finally, centrifugation, washing, and drying are performed to obtain the cationic starch ether.
[0048] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.
[0049] Example 1
[0050] A method for preparing a gypsum-based slurry composite rock wool clean board core material comprises the following steps:
[0051] (1) 900 kg of gypsum, 0.3 kg of hydroxypropyl starch ether (molecular weight of 50,000, degree of substitution of 0.3), 1 kg of rubber powder, 2 kg of polycarboxylate water reducer, 2 kg of sodium citrate, and 1 kg of modified glass fiber were mixed to obtain a dry powder mixture, and then 400 kg of water was added and mixed to obtain a gypsum-based slurry;
[0052] (2) Lay the first layer of glass fiber mesh (weight per unit area is 130g / m 2 ), pouring gypsum slurry, the mass ratio of glass fiber mesh to gypsum-based slurry is 100:1, forming an upper panel with a thickness of 0.5 cm;
[0053] (3) Rock wool strips are placed on the upper panel surface, and the rock wool strips are laid in an alternating manner to form a rock wool core board with a thickness of 3.85 cm;
[0054] (4) Laying a second layer of glass fiber mesh, pouring gypsum slurry on the surface of the rock wool to form a lower panel (with the same specifications as the upper panel), and drying to obtain the gypsum-based slurry composite rock wool clean board core material.
[0055] Wherein, the gypsum is a composition of α-semi-hydrated desulfurized gypsum powder and phosphogypsum powder in a mass ratio of 1:0.2;
[0056] The modified glass fiber is prepared by the following method:
[0057] 70g of vinyltrimethoxysilane was dissolved in 10 times by weight of ethanol aqueous solution (ethanol mass fraction was 20%) to obtain a coupling agent solution; 1kg of glass fiber was added into the coupling agent solution to react for 2h, and after the reaction was completed, the solution was taken out and dried to obtain a coupling agent modified glass fiber; 20g of 4-phenyl-3-butenoic acid was dissolved in 10 times by weight of propylene glycol, and then the coupling agent modified glass fiber was added, and 0.1g of azobisisobutyronitrile was added to react for 2h, and after the reaction was completed, the solution was taken out and dried to obtain the modified glass fiber.
[0058] Example 2
[0059] A method for preparing a gypsum-based slurry composite rock wool clean board core material comprises the following steps:
[0060] (1) 950 kg of gypsum, 0.45 kg of hydroxypropyl starch ether (molecular weight of 100,000, degree of substitution of 0.7), 2 kg of rubber powder, 3 kg of polycarboxylate water reducer, 3 kg of potassium tartrate, and 2.5 kg of modified glass fiber were mixed to obtain a dry powder mixture, and then 500 kg of water was added and mixed to obtain a gypsum-based slurry;
[0061] (2) Laying the first layer of glass fiber mesh (weight per unit area is 140g / m 2), pouring gypsum slurry, the mass ratio of glass fiber mesh to gypsum-based slurry is 100:1.3, forming an upper panel with a thickness of 0.5 cm;
[0062] (3) Rock wool strips are placed on the upper panel surface, and the rock wool strips are laid in an alternating manner to form a rock wool core board with a thickness of 3.85 cm;
[0063] (4) Laying a second layer of glass fiber mesh, pouring gypsum slurry on the surface of the rock wool to form a lower panel (with the same specifications as the upper panel), and drying to obtain the gypsum-based slurry composite rock wool clean board core material.
[0064] Wherein, the gypsum is a composition of α-semi-hydrated desulfurized gypsum powder and phosphogypsum powder in a mass ratio of 1:0.27;
[0065] The modified glass fiber is prepared by the following method:
[0066] Dissolve 85g of vinyl triisopropoxysilane in 10 times by weight of ethanol aqueous solution (ethanol mass fraction is 20%) to obtain a coupling agent solution; add 1kg of glass fiber into the coupling agent solution to react for 4 hours, take out and dry after the reaction is completed to obtain coupling agent modified glass fiber; dissolve 30g of 4-phenyl-3-butenoic acid in 10 times by weight of propylene glycol, then add the coupling agent modified glass fiber, add 0.5g of azobisisobutyronitrile to react for 4 hours, take out and dry after the reaction is completed to obtain the modified glass fiber.
[0067] Example 3
[0068] A method for preparing a gypsum-based slurry composite rock wool clean board core material comprises the following steps:
[0069] (1) 960 kg of gypsum, 0.6 kg of hydroxypropyl starch ether (molecular weight of 200,000, degree of substitution of 1.2), 3 kg of rubber powder, 3.5 kg of polycarboxylate water reducer, 3.5 kg of potassium tartrate, and 3.5 kg of modified glass fiber were mixed to obtain a dry powder mixture, and then 560 kg of water was added and mixed to obtain a gypsum-based slurry;
[0070] (2) Lay the first layer of glass fiber mesh (weight per unit area is 160g / m 2 ), pouring gypsum slurry, the mass ratio of glass fiber mesh to gypsum-based slurry is 100:1.3, forming an upper panel with a thickness of 0.5 cm;
[0071] (3) Rock wool strips are placed on the upper panel surface, and the rock wool strips are laid in an alternating manner to form a rock wool core board with a thickness of 3.85 cm;
[0072] (4) Laying a second layer of glass fiber mesh, pouring gypsum slurry on the surface of the rock wool to form a lower panel (with the same specifications as the upper panel), and drying to obtain the gypsum-based slurry composite rock wool clean board core material.
[0073] Wherein, the gypsum is a composition of α-semi-hydrated desulfurized gypsum powder and phosphogypsum powder in a mass ratio of 1:0.3;
[0074] The modified glass fiber is prepared by the following method:
[0075] 100g of vinyl triisopropoxysilane is dissolved in 10 times by weight of ethanol aqueous solution (ethanol mass fraction is 20%) to obtain a coupling agent solution; 1kg of glass fiber is added into the coupling agent solution to react for 4h, and after the reaction is completed, it is taken out and dried to obtain a coupling agent modified glass fiber; 35g of 4-phenyl-3-butenoic acid is dissolved in 10 times by weight of propylene glycol, and then the coupling agent is added to modify the glass fiber, and 0.5g of azobisisobutyronitrile is added to react for 4h, and after the reaction is completed, it is taken out and dried to obtain the modified glass fiber.
[0076] Example 4
[0077] A method for preparing a gypsum-based slurry composite rock wool clean board core material comprises the following steps:
[0078] (1) 960 kg of gypsum, 0.6 kg of hydroxypropyl starch ether (molecular weight of 100,000, degree of substitution of 0.8), 3 kg of rubber powder, 3.5 kg of polycarboxylate water reducer, 3.5 kg of potassium tartrate, and 3.5 kg of modified glass fiber were mixed to obtain a dry powder mixture, and then 600 kg of water was added and mixed to obtain a gypsum-based slurry;
[0079] (2) Lay the first layer of glass fiber mesh (weight per unit area is 160g / m 2 ), pouring gypsum slurry, the mass ratio of glass fiber mesh to gypsum-based slurry is 100:1.5, forming an upper panel with a thickness of 0.5 cm;
[0080] (3) Rock wool strips are placed on the upper panel surface, and the rock wool strips are laid in an alternating manner to form a rock wool core board with a thickness of 3.85 cm;
[0081] (4) Laying a second layer of glass fiber mesh, pouring gypsum slurry on the surface of the rock wool to form a lower panel (with the same specifications as the upper panel), and drying to obtain the gypsum-based slurry composite rock wool clean board core material.
[0082] Wherein, the gypsum is a composition of α-semi-hydrated desulfurized gypsum powder and phosphogypsum powder in a mass ratio of 1:0.35;
[0083] The modified glass fiber is prepared by the following method:
[0084] 120g of vinyl triethoxysilane was dissolved in 10 times by weight of ethanol aqueous solution (ethanol mass fraction is 20%) to obtain a coupling agent solution; 1kg of glass fiber was added into the coupling agent solution to react for 4h, and after the reaction was completed, it was taken out and dried to obtain a coupling agent modified glass fiber; 50g of 4-phenyl-3-butenoic acid was dissolved in 10 times by weight of propylene glycol, and then the coupling agent modified glass fiber was added, and 0.5g of azobisisobutyronitrile was added to react for 4h, and after the reaction was completed, it was taken out and dried to obtain the modified glass fiber.
[0085] Example 5
[0086] The difference between this embodiment and embodiment 2 is that the gypsum is a composition of α-semi-hydrated desulfurized gypsum powder and phosphogypsum powder in a mass ratio of 1:0.1, and the total amount remains unchanged.
[0087] Example 6
[0088] The difference between this embodiment and embodiment 2 is that the gypsum is a composition of α-semi-hydrated desulfurized gypsum powder and phosphogypsum powder in a mass ratio of 1:0.5, and the total amount remains unchanged.
[0089] Example 7
[0090] The difference between this embodiment and embodiment 2 is that the gypsum is only α-semi-hydrate desulfurized gypsum powder, and the total amount remains unchanged.
[0091] Example 8
[0092] The difference between this embodiment and embodiment 2 is that the gypsum is only phosphogypsum powder, and the total amount remains unchanged.
[0093] Example 9
[0094] The difference between this embodiment and embodiment 2 is that the α-semi-hydrated desulfurized gypsum powder in the gypsum is replaced by an equal amount of β-semi-hydrated desulfurized gypsum powder.
[0095] Example 10
[0096] The difference between this embodiment and embodiment 2 is that the starch ether is replaced by an equal amount of a hydroxypropyl starch ether and a cationic starch ether composition in a mass ratio of 10:1.5; wherein,
[0097] The degree of substitution of hydroxypropyl starch ether is 0.7 and the molecular weight is 100,000;
[0098] The degree of substitution of cationic starch ether is 0.3 and the molecular weight is 50,000.
[0099] Embodiment 11
[0100] The difference between this embodiment and embodiment 3 is that the starch ether is replaced by an equal amount of a hydroxypropyl starch ether and a cationic starch ether composition in a mass ratio of 10:4; wherein,
[0101] The degree of substitution of hydroxypropyl starch ether is 1.2 and the molecular weight is 200,000;
[0102] The degree of substitution of cationic starch ether is 0.6 and the molecular weight is 100,000.
[0103] Example 12
[0104] The difference between this embodiment and embodiment 10 is that the mass ratio of hydroxypropyl starch ether to cationic starch ether is 10:1.
[0105] Example 13
[0106] The difference between this embodiment and embodiment 10 is that the mass ratio of hydroxypropyl starch ether to cationic starch ether is 10:5.
[0107] Embodiment 14
[0108] The difference between this embodiment and embodiment 10 is that the starch ether is replaced by an equal amount of cationic starch ether.
[0109] Comparative Example 1
[0110] The difference between this comparative example and Example 2 is that during the preparation of the modified glass fiber, 4-phenyl-3-butenoic acid is replaced by an equal amount of acrylic acid.
[0111] Comparative Example 2
[0112] The difference between this comparative example and Example 2 is that an equal amount of coupling agent-modified glass fiber is used instead of the modified glass fiber, and the preparation method of the coupling agent-modified glass fiber is the same as that of Example 2.
[0113] Comparative Example 3
[0114] The difference between this comparative example and Example 2 is that an equal amount of unmodified glass fibers are used instead of modified glass fibers.
[0115] Test Example 1
[0116] The mechanical properties and combustion performance of the clean board core materials prepared in the above embodiments and comparative examples were tested, and the results are shown in Table 1 below.
[0117] Table 1
[0118]
[0119]
[0120] The results show that the clean board core material prepared by the present invention has high compressive strength, low thermal conductivity, good thermal insulation, a fire resistance limit of more than 1.5h, a combustion grade of A, and good flame resistance.
[0121] Test Example 2
[0122] Corrosion resistance
[0123] The clean board core materials prepared in the above-mentioned embodiment and comparative example were immersed in a 10% by mass hydrochloric acid solution and a 10% by mass sodium hydroxide solution for 48 hours, respectively, and their compressive strength was tested. The results are shown in Table 3 below.
[0124] Table 2
[0125] Group (After immersion in sodium hydroxide) compressive strength MPa (After hydrochloric acid immersion) compressive strength MPa Example 1 2.21 2.25 Example 2 2.46 2.50 Example 3 2.27 2.34 Example 4 2.19 2.28 Example 5 1.80 1.86 Example 6 1.64 1.72 Example 7 1.91 1.92 Example 8 1.21 1.54 Example 9 1.60 1.67 Example 10 3.37 3.40 Embodiment 11 3.29 3.31 Example 12 2.21 2.25 Example 13 2.29 2.33 Embodiment 14 1.40 1.47 Comparative Example 1 0.92 1.04 Comparative Example 2 0.87 0.96 Comparative Example 3 0.68 0.74
[0126] Tests have found that the clean board core material prepared in the embodiment of the present invention will not crack, peel or fall off after being immersed in hydrochloric acid or sodium hydroxide solution for a long time, and the compressive strength does not decrease significantly, indicating that it has good corrosion resistance.
[0127] However, the clean board core material prepared in the comparative example peeled off after being immersed in hydrochloric acid or sodium hydroxide solution for a long time, and its compressive strength dropped significantly, and its corrosion resistance was poor.
[0128] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A gypsum-based slurry composite rock wool clean board core material, characterized in that: It comprises: a rock wool core board, and upper and lower panels formed by pouring gypsum-based slurry on both sides of the rock wool core board and embedding alkali-resistant glass fiber mesh; wherein, The gypsum-based slurry comprises the following raw materials in terms of weight: 900-980 parts of gypsum, 0.3-0.8 parts of starch ether, 1-4 parts of rubber powder, 2-4 parts of water reducer, 2-4 parts of retarder, 1-5 parts of modified glass fiber, and 400-600 parts of water; The modified glass fiber is prepared by using glass fiber as raw material and sequentially modified by a double-bond silane coupling agent and 4-phenyl-3-butenoic acid; the mass ratio of the double-bond coupling agent to the glass fiber is (7-12):100; the mass ratio of the 4-phenyl-3-butenoic acid to the glass fiber is (2-5):100; The starch ether is a composition of hydroxyalkyl starch ether and cationic starch ether, wherein the mass ratio of the hydroxyalkyl starch ether and the cationic starch ether is 10:(1.5-4); The gypsum is a combination of α-semi-hydrated desulfurized gypsum powder and phosphogypsum powder; the mass ratio of the α-semi-hydrated desulfurized gypsum powder to the phosphogypsum powder is 1:(0.2-0.35).
2. The gypsum-based slurry composite rock wool clean board core material according to claim 1, characterized in that: The mass ratio of the gypsum-based slurry to the glass fiber mesh in the upper and lower panels is 100:(1-1.5); the ratio of the total thickness of the upper and lower panels to the thickness of the rock wool core board is 1:(3-8).
3. The gypsum-based slurry composite rock wool clean board core material according to claim 1, characterized in that: The hydroxyalkyl starch ether is hydroxyethyl starch ether or hydroxypropyl starch ether; the degree of substitution of the hydroxyalkyl starch ether is 0.7 to 1.2, and the molecular weight is 100,000 to 200,000; The cationic starch ether is prepared by etherifying and modifying corn starch using 3-chloro-2-hydroxypropyltrimethylammonium chloride as an etherifying agent; the substitution degree of the cationic starch ether is 0.3-0.6 and the molecular weight is 50,000-100,000.
4. The method for preparing the gypsum-based slurry composite rock wool clean board core material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Mixing the components in the gypsum-based slurry to obtain a dry powder mixture, and then adding water to mix to obtain a gypsum-based slurry; (2) Laying the first layer of glass fiber mesh and pouring gypsum slurry to form the upper panel; (3) Place rock wool strips on the surface of the upper panel to form a rock wool core board; (4) Laying a second layer of glass fiber mesh, pouring gypsum slurry on the surface of the rock wool core board to form a lower panel, and drying it to obtain the gypsum-based slurry composite rock wool clean board core material.
Citation Information
Patent Citations
High-strength water-resistant glass-fiber-reinforced / toughened gypsum board and preparation method thereof
CN107226668A
Novel heat preservation and heat insulation integrated gypsum wallboard and manufacturing method thereof
CN113502976A